Direct‐Contact Heat Transfer during n‐Pentane Vaporization in a Two‐Dimensional Water Column. Issue 7 (7th April 2020) - Fu, Hailing; Ma, Lianjie; Wang, Haiyan
Abstract: Direct‐contact vaporization heat transfer is investigated by analyzing the heat transfer coefficient with the area of liquid‐liquid direct‐contact interface. The interface areas of liquid‐liquid heat transfer are determined by stroboscopic images. At higher temperature, the heat transfer area per unit volume decreases. The water temperature has no significant influence on the heat transfer coefficient. The effects on droplet size distributions of operating variables including inlet water temperature, n ‐pentane flow rate, and test position with packing and without packing are compared. Abstract : A visualization experiment was performed to investigate the evaporation of n ‐pentane droplet swarms in a two‐dimensional column filled with hot water. The liquid‐liquid heat transfer interfacial areas of all evaporative droplets and the heat transfer coefficients of single droplets were determined. The droplet size distributions were described using the probability density function.